TATA KELOLA PEMERINTAHAN YANG BAIK DALAM PELAYANAN PUBLIK DI KANTOR LURAH WONGKADITI TIMUR KECAMATAN KOTA UTARA - Juriko Abdussamad; Mochammad Sakir; Swastiani Dunggio (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to determine the application of the principles of good governance in public services at the East Wongkaditi Village Head Office, Kota Utara District. In this study, researcher used descriptive research methods with a qualitative approach, namely research that aims to provide an overview of the application of the principles of good governance in public services in the East Wongkaditi Lurah Office, Kota Utara District. The determination of the informants was carried out using a purposive sampling technique, and the selected informants were village heads, youth leaders, 2 community leaders, and 4 people from the community. The results of the study indicate that the application of the principles of good governance in public services at the East Wongkaditi Lurah Office, North Kota District, has not been maximally implemented by village officials. This can be seen from the three indicators studied, namely accountability, transparency and community participation in the administration of public services in the East Wongkaditi Village, all of these three indicators have not been implemented properly by the apparatus.